2021
DOI: 10.3389/fpsyg.2021.697373
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional and Intersectional Gender Identity and Sexual Attraction Patterns of Adolescents for Quantitative Research

Abstract: To identify and compare gender identity and sexual attraction (GISA) patterns using a latent class analysis (LCA), questionnaire data from a cross-sectional study on social resilience in adolescence was conducted in 2020, using a sample of 785 Swiss seventh grade high school students. Following McCall’s complex intersectionality approach, we applied an intracategorical and intersectional approach to reshape, differentiate, and critique the existing binary, heteronormative GISA categorization. To empirically va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 96 publications
0
4
1
Order By: Relevance
“…As there are different forms of social rejection that affect boys and girls differently, it would be important for future research to examine the specific forms of rejection using an intersectional framework. Previous research has been shown that a binary assessment of gender does not provide sufficient insights into developmental trajectories and therefore into the cycle of violence (Kassis et al, 2021). Dissociation showed no effect, which is why Hypothesis 2 could not be confirmed in our results.…”
Section: Discussioncontrasting
confidence: 81%
“…As there are different forms of social rejection that affect boys and girls differently, it would be important for future research to examine the specific forms of rejection using an intersectional framework. Previous research has been shown that a binary assessment of gender does not provide sufficient insights into developmental trajectories and therefore into the cycle of violence (Kassis et al, 2021). Dissociation showed no effect, which is why Hypothesis 2 could not be confirmed in our results.…”
Section: Discussioncontrasting
confidence: 81%
“…Other international studies identifying SES and familial wealth as not being predictors of parental physical abuse [1,3,7] corroborate our results. We still have to take into consideration that testing gender as binary, as we did, still results in an enormous reduction of the existing gender variations and requires an intersectional approach [117].…”
Section: Discussionmentioning
confidence: 99%
“…Although the study, in comparison to other studies, took into account individual characteristics, recent studies exist that reveal how the categorization of sociodemographic variables in current research falls short. As Kassis et al (2021) have recently shown, thanks to person-centered gender identity and sexual attraction classes, psychosocial status can be mapped in a far more heterogeneous and detailed manner when multidimensional gender identity is considered rather than assigned sex. A more intersectional analysis of youths who have experienced violence would be another way for future research to fully explore the issue.…”
Section: Discussionmentioning
confidence: 99%